Pertanggungjawaban Debitur Terhadap Kreditur Pada Perjanjian Kredit Dengan Jaminan Fidusia - Rizka Astri Husen; Nancy Silvana Haliwela; Agustina Balik (PATTIMURA Law Study Review, 2023)
ABSTRACT: An agreement is an agreement made by one party and another party based on trust. It is the same with credit agreements with fiduciary guarantees that occur between debtors, creditors and third parties. Where a third party defaults, against the creditor. by not paying car loan installments. So that it results in a credit agreement between the Debtor and the Creditor. So that the action refers to the provisions of the Civil Code Article 1238, namely "The debtor is declared negligent by a warrant, or by a similar deed, or based on the strength of the agreement itself, that is, if this agreement results in the debtor being deemed negligent within the allotted time". The type of research used is normative juridical research. the type of normative juridical research is a research that examines legal materials, legal doctrine, legal principles, legal principles, as well as positive legal provisions in order to answer the legal issues that have been studied. Another name for normative research is doctrinal legal research which can be referred to as library research or document study because this research is carried out and shown only on written regulations or other legal materials. The results of the study show that it is related to credit accountability. From debtors, creditors and third parties. The responsibility of the debtor to the creditor is based on Article 30 of the Fiduciary Law that the debtor will hand over fiduciary objects to the creditor. Settlement of defaults can be carried out through litigation or non-litigation between the debtor and the creditor. then the legal settlement between the debtor and a third party, by making a warning letter or a new agreement for the losses suffered by the debtor.